THE ROLE OF PARENTS IN IMPLEMENTING THE 7 HABITS OF GREAT INDONESIAN CHILDREN IN ELEMENTARY SCHOOL - Naila Putri Akbar; Mashud -; Recky Ahmad Haffyandi (Universitas Islam Kalimantan Muhammad Arsyad Al Banjari, 2025)
The purpose of this study is to explore how the role of parents contributes to the implementation of the 7 habits of great Indonesian children at school, especially in the aspect of sports activities of elementary school-age children. The program emphasizes the importance of positive habits that shape children's character from an early age, such as Sleeping Early, Waking Up Early, Worship, Exercise, Healthy and Nutritious Eating, Love to Learn, and Community. The research used mixed methods with quantitative and qualitative approaches through explanatory sequential design. The research sample consisted of 91 parents of SDN 2 South Loktabat students for quantitative data and 9 people for qualitative data. The results show that the role of parents is in the “enough” to “good” category in various indicators such as involvement, support and role modeling. While the awareness of the importance of exercise is there, consistent and comprehensive implementation remains a challenge. Synergy between parents and schools is needed to create sustainable positive habits to support character building and children's health.